(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The use of coolants while machining was reduced because of the problems encountered by it like environmental pollution, health hazards and high setup costs. The present work, deals with the comparison of experimental, geometrical and regression values of surface roughness during CNC turning of AA7075 steel with tungsten carbide tool. The experiments were done on CNC lathe as per Taguchi’s standard L9 (3^3) orthogonal array. Cutting speed, feed and depth of cut were taken as inputs at three different levels and surface roughness characteristics Ra, Rq and Rz were considered as outputs. Mathematical models were developed for Ra, Rq and Rz using the MINITAB-16 software and good correlation was found between input parameters and the output characteristics. Hence the models prepared can be used for better prediction of the responses. ANOVA was employed to test the significance of the model prepared. Finally, the experimental values were compared with both the regression and available geometrical model values and the comparison plots were drawn using EXCEL